AN ANALYTICAL MODEL FOR PREDICTION OF CONTROLLED RELEASE FROM BULK BIODEGRADING POLYMER MICROSPHERES - Sivandzade, Farzane (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: A convenient numerical model has been developed to predict release profile of different types of agents from bulk biodegrading polymer microspheres, including magnitude methods are less accurate than analytical methods. Usually, this study used analytical solutions for the model and compared the analytical results with numerical solution and experimental data. Methods: The objective drug controlled release profiles were modeled based on a four-phase pattern. Then, a specific formulation was considered based on Fick's second law. After calculating various parameters, the equations were solved using an analytical method. Results: Comparison results showed that analytical solution can reproduce experimental behavior of controlled release systems with a higher accuracy. Conclusion: Although in previous work, drug release profile from a polymer matrix composed of poly lactic-co-glycolic acid was predicted using readily attainable parameters and representing tunable matrix properties by a numerical method, the proposed analytical method can give more accurate results compared to the numerical method.